UNDERWATER ERUPTION IN THE AKADEMII NAUK CALDERA, KAMCHATKA AND ITS CONSEQUENCES: IMPLICATIONS FROM HYDROGEOLOGICAL, HYDROCHEMICAL AND HYDROBIOLOGICAL STUDIES - Fazlullin S.M.; Ushakov S.V.; Shuvalov R.A.; Aoki M.; Nikolaeva A.G.; Lupikina E.G. (My University, 2001)
This paper presents the results of hydrochemical, hydrological, and hydrobiological studies that were conducted in Lake Karymskii in connection with an underwater eruption that had occurred in January 1996. Also presented here are data on the chemical and isotopic composition of water from the Akademii Nauk caldera. This paper also describes the vertical temperature distribution in the flooded crater and in the open lake and the lake level variations in 1996. First data are presented on changes in the biota species after the eruption.